Preparation and Characterization of Vancomycin Hydrochloride-Loaded Mesoporous Silica Composite Hydrogels - Sun, Ming; Cheng, Lidi; Xu, Zexian; Chen, Liqiang; Liu, Yanshan; Xu, Yaoxiang; Zhou, Dongyang; Zhang, Xiuxiu; Zhou, Qihui; Sun, Jian (Frontiers in Bioengineering and Biotechnology, 2022)
This paper aims to explore the feasibility of the novel temperature-sensitive hydrogel-based dual sustained-release system (Van/SBA-15/CS-GP-SA) in the repair and treatment of infectious jaw defects. Van/SBA-15 was prepared using mesoporous silica material (SBA-15) as a carrier for vancomycin hydrochloride (Van), and Van/SBA-15 was characterized by scanning electron microscopy (SEM), transmission electron microscopy (TEM), energy dispersive spectrometry (EDS), X-ray photoelectron spectroscopy (XPS), Fourier transform infrared (FTIR)，Brunauer-Emmett-Teller (BET) and Barrett-Joyner-Halenda (BJH). Van/SBA-15/CS-GP-SA was constructed by encapsulating Van/SBA-15 in chitosan-sodium glycerophosphate-sodium alginate hydrogel (CS-GP-SA). The microstructures, sustained-release ability, biocompatibility, and antibacterial property of Van/SBA-15/CS-GP-SA were systematically studied. Van/SBA-15/CS-GP-SA was found to have the promising sustained-release ability, outstanding biocompatibility, and excellent antibacterial property. This study provides new ideas for management of infectious jaw defects.